Computer Aided Decision Making in Social Forestry - Marathe, Ashok; Ghate, Vinaya; Abhyankar, Promod; Vartak, V. D. (Indian Forester, 1991)
The paper presents computerized botanical data on Indigenous arboreal flora of Weatern Maharashtra. Phonological, climatic, distributional and utilitarian attributes for 273 indigenous tree species have been analyaed using data base. The stored data can be utilized with variety of character combinations to serve multiple applications as and when required. This computer aided decision making would help In selection of suitable species for planning and Implementation of Social Forestry Programmes with preferential habitats of plantation.